KONSEP KEADILAN DALAM ZAKAT PERTANIAN DAN ZAKAT PROFESI - Wahyuni; Rahman Ambo Masse; Rukiah (Institut Agama Islam Negeri Parepare, 2020)
One of the economic activities that is highly recommended by Islam is zakat. Al-Qur'an and hadith explain a lot about zakat, where zakat is very important and it is recommended to clean up wealth. In addition, the wealth spent on zakat will be a blessing, growth, increase and develop. The concept of fairness in collecting zakat includes several things, namely using the principle of justice in distribution. the assets issued fulfill the terms and conditions and then the zakat is given to groups which are entitled to receive. This study aims to determine how the concept of justice in agricultural zakat and professional zakat, where this research uses a library approach and uses data collection methods and data processing validly. Justice in agricultural zakat and professional zakat is justice based on two principles of justice (commutative justice and distributive justice). Agricultural Zakat is zakat of agricultural products such as cloves, cocoa, coffee, vegetables and can be stored for a long time removed from the harvest and has reached nishab which is 5% if the crop is irrigated with irrigation equipment and if the crop is irrigated with rainfed then the zakat is 10 % and does not have to pay zakat if it does not reach nishab. While professional zakat is zakat resulting from the thoughts, skills and expertise of a person obtained through higher education levels such as (advocates, lawyers, doctors, engineers, etc.) and has reached 2.5% of nishab, the proportion of which is equal to gold zakat and has also been equal reach haul. If the income does not reach nishab, it is not obligatory for it to pay zakat